2021
DOI: 10.1002/ajpa.24220
|View full text |Cite
|
Sign up to set email alerts
|

Dietary changes across time: Studying the indigenous period of La Gomera using δ13C and δ15N stable isotope analysis and radiocarbon dating

Abstract: Objectives This article presents new radiocarbon and isotopic data to provide further information about the diet of the indigenous population of La Gomera and its possible changes across time. Materials and methods δ13C and δ15N of 53 human and 19 faunal samples from different sites on the island have been obtained and analyzed. Of these, 52 have been radiocarbon dated to provide insight on chronological changes. Results Human dates range from the 3rd to 15th centuries AD, while faunal dates range from the 1st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
(83 reference statements)
1
8
0
Order By: Relevance
“…The primary source of dietary protein has been suggested to be mainly terrestrial in the whole archipelago, except for the case of the site of La Lajura , in El Hierro Island (Arnay‐de‐la‐Rosa et al, 2010). Likewise, δ 13 C values are predominantly related to a C3 plant environment both in our sample and in all previous studies done in the archipelago (Arnay‐de‐la‐Rosa et al, 2009; 2010; 2011; Lécuyer et al, 2021; Sánchez‐Cañadillas et al, 2021; Tieszen et al, 1995). If the marine contribution to the diet was higher, it would be expected to find higher values in δ 13 C isotopes due to the marine carbon reservoir being added to the consumers' tissues, as is the case of isotopic studies done on islanders from the Pacific (Kinaston et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The primary source of dietary protein has been suggested to be mainly terrestrial in the whole archipelago, except for the case of the site of La Lajura , in El Hierro Island (Arnay‐de‐la‐Rosa et al, 2010). Likewise, δ 13 C values are predominantly related to a C3 plant environment both in our sample and in all previous studies done in the archipelago (Arnay‐de‐la‐Rosa et al, 2009; 2010; 2011; Lécuyer et al, 2021; Sánchez‐Cañadillas et al, 2021; Tieszen et al, 1995). If the marine contribution to the diet was higher, it would be expected to find higher values in δ 13 C isotopes due to the marine carbon reservoir being added to the consumers' tissues, as is the case of isotopic studies done on islanders from the Pacific (Kinaston et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, the indigenous population occupied the islands during more than 1000 years (Velasco‐Vázquez et al, 2019), and while their diet was likely based on the same resources, it probably was not homogeneous in the proportions of those resources. Small differences are expected to appear depending on islands (Arnay‐de‐la‐Rosa et al, 2010), time periods (Lécuyer et al, 2021; Sánchez‐Cañadillas et al, 2021), or even local differences on each island, as evidenced by this study. This study has focused on the later period, albeit with one sample belonging to a funerary context with a wide timeframe, that being GRAN‐02 ( Guayadeque ), the differences of this profile compared with GRAN‐01 ( El Metropole ) could be both related to local variations (terrestrial vs. mixed‐diet) and chronological variations (different centuries).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…For samples displaying evidence of a marine diet, both the diet correction and the reservoir effect should be applied prior to calibration. In this regard, a recent study on stable isotopes for the island of La Gomera has identified a human dietary evolution whose first stage principal contribution was marine (Sánchez-Cañadillas et al, 2021).…”
Section: A Proposal For a Radiometric Hygiene Protocolmentioning
confidence: 99%